A highly porous medical metal–organic framework constructed from bioactive curcumin. Issue 26 (27th February 2015) - Su, Hongmin; Sun, Fuxing; Jia, Jiangtao; He, Hongming; Wang, Aifei; Zhu, Guangshan
Abstract : A highly porous bio-MOF, medi-MOF-1, constructed from Zn and curcumin has been successfully synthesized, which exhibits great potential in bioapplications. Abstract : A highly porous bio-MOF, medi-MOF-1, constructed from Zn and the pharmaceutical ingredient curcumin has been successfully synthesized. It can display permanent porosity with a surface area as high as ca. 3002 m 2 g −1, which exhibits great potential in bioapplications. Its ibuprofen delivery ability, biodegradation and cytotoxicity were also studied.